2007
DOI: 10.1097/bot.0b013e31802cbc54
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Negative-Pressure Wound Therapy (NPWT) in the Temporary Treatment of Soft-Tissue Injuries Associated With High-Energy Open Tibial Shaft Fractures

Abstract: Infection and nonunion rates with the use of NPWT for temporary coverage of wounds associated with grade/type III open tibial shaft fractures are similar to those of historical controls, but this technique may be beneficial in decreasing the need for free tissue transfer or rotational muscle flap coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 20 publications
2
94
0
3
Order By: Relevance
“…Pediatric studies were not excluded. Thirteen studies remained [6,7,15,16,29,30,33,35,36,45,47,49,50] after reading the abstract and the full-length article as needed to ascertain data points. Twenty-two studies were eliminated from the final 35 articles identified because they were review articles (n = 8), articles regarding pilon fracture (n = 2), and articles with insufficient data or case reports (n = 12).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 4 more Smart Citations
“…Pediatric studies were not excluded. Thirteen studies remained [6,7,15,16,29,30,33,35,36,45,47,49,50] after reading the abstract and the full-length article as needed to ascertain data points. Twenty-two studies were eliminated from the final 35 articles identified because they were review articles (n = 8), articles regarding pilon fracture (n = 2), and articles with insufficient data or case reports (n = 12).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…All publications were from 2006 and later, likely owing to FDA approval in 1997 and several years thereafter for clinicians to use negative pressure wound therapy and several more years for patient followup. One of the 13 studies was an RCT [49], and the remaining 12 were retrospective [6,7,15,16,29,30,33,35,36,45,47,50]. The RCT was not eliminated because of lack of study quality as defined by Moher et al [37] or by Detsky et al [17].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 3 more Smart Citations